Answer:
Step-by-step explanation:
The most general form of this, without seeing any of the options, would be:
[tex]y=(x+3)^2+6[/tex]
Again, there might have been a value outside the parenthesis that may or may not have been negative, but either way, this is the most basic translation of the parabola.
#8 Dylan, Mike and Jeremy had $171. Mike had twice as much money as Dylan. Jeremy had three times as much money as Mike. How much money did Jeremy have?
#9 we skipped this one
#10. Maddy had twice as many stamps as Simon. After Maddy sold 60 stamps, Sinom had twice as many stamps as Maddy. How many more stamps did Maddy have than Simon in the beginning?
Answer:
8. $114
10. 60 stamps
Step-by-step explanation:
8.
Let Dylan have d, Mike have m, and Jeremy have j
3 of them have 171, so we can write:
1. [tex]d + m + j = 171[/tex]
Mike has twice as Dylan, so we can write:
2. m = 2d
Jeremy had three times as Mike, so:
3. j = 3m
We can write equation 3 as m = j/3
Also, if we put this into equation 2, we have:
j/3=2d
d=j/6
Now we have d and m in terms of j. We put it into equation 1 and solve for j:
[tex]\frac{j}{6} + \frac{j}{3} + j = 171\\\frac{3j+6j+18j}{18}=171\\\frac{27j}{18}=171\\27j=18*171\\27j=3078\\j=\frac{3078}{27}\\j=114[/tex]
Jaime has $114
10.
amount of stamps Maddy has is m and amount Simon has is s
Maddy had twice as many stamps as Simon:
m = 2s
Also
After Maddy sold 60 stamps, Sinom had twice as many stamps as Maddy:
s+60=2(m-60)
We put the first equation in the second and solve for s:
s+60=2(m-60)
s+60=2(2s-60)
s+60=4s-120
180=3s
s=60
THus, m = 2(60) = 120
So maddy had 120 - 60 = 60 more stamps than Simon
A stained glass window is going to be installed in a semi-circular opening, which is above a 34 inch wide door. If the stained glass window costs $0.95 per square inch, how much will the window cost? Use 3.14 for π
as necessary.
A. $389.10
B. $1,724.17
C. $431.04
D. $494.55
The area of a full circle would be Area = PI x r^2
The diameter would be the width of the dorr, so the radius would be half that. 34/2 = 17 inches.
Area for a full circle would be 3.14 x 17^2 = 907.46 square inches.
A semi circle is a half circle.
The area would be 907.46 / 2 = 453.73 square inches.
Multiply the area by the cost:
453.73 x 0.95 = 431.04
The answer is C.
Final answer:
To find the cost of the stained glass window, calculate the area of a 34-inch diameter semi-circular window, and then multiply that by the cost per square inch ($0.95). The total cost is approximately $431.17.
Explanation:
To calculate the cost of the stained glass window, we must first find the area of the semi-circular window above the door. Since the width of the door is 34 inches, the diameter of the semi-circle is also 34 inches, which means the radius (r) is half of that, or 17 inches.
Step 1: Calculate the area of the semi-circle
The formula for the area of a circle is A = πr². For a semi-circle, it would be half of that area, so the formula changes to A = (πr²) / 2.
Plugging in the radius, we get A = (3.14 * (17²)) / 2 = (3.14 * 289) / 2 = 453.86 square inches.
Step 2: Calculate the cost of the stained glass
The cost per square inch is $0.95. Multiplying the area by the cost per square inch, we get Total Cost = 453.86 * $0.95 = $431.167, which rounds to $431.17.
The closest cost option given is C. $431.04.
What is the point of intersection when the system of equations below is graphed on the coordinate plane?
x-y=1 and y-x=1
Answer:
not existStep-by-step explanation:
The coordinates of the intersection of the line are the solution of the system of equations.
[tex]\underline{+\left\{\begin{array}{ccc}x-y=1\\y-x=1\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad\qquad0=2\qquad\bold{FALSE}[/tex]
The system of equations has no solution. Therefore, the lines are parallel (the intersection does not exist).
Which of the following is the product of the rational expressions shown
below?
O A. 28 2 4
O B.220
Occhia
O D. 22 + 4x
Answer:
21/2x^2+4x
Step-by-step explanation:
What is the approximate value of x in the equation below.
log3/4 25 =3x-1
–3.396
–0.708
0.304
0.955
Answer:
- 3.396
Step-by-step explanation:
Given equation is,
[tex]log_{\frac{3}{4}} 25 = 3x-1[/tex]
By using logarithm property,
[tex]log_ax=\frac{log_bx}{log_ba}[/tex]
We get,
[tex]\frac{log25}{log\frac{3}{4}}=3x-1[/tex]
[tex]\frac{1.39794000867}{-0.124938736608}=3x-1[/tex]
[tex]-11.18900388=3x-1[/tex]
Adding 1 on both sides,
[tex]-10.18900388=3x[/tex]
[tex]\implies x = -\frac{10.18900388}{3}=-3.39633462667\approx -3.396[/tex]
Hence, the approximate value of x is -3.396.
First option is correct.
Answer: They might switch options around but if not...
Option A) -3.396
What is the answer help me
Find the product of (4x + 3y)(4x − 3y). (2 points)
(4x+3y)(4x-3y)
Multiply the two brackets together
4x(4x)(4x-3y)(-3y)(4x)(3y)(-3y)
16x^2-12xy+12xy-9y^2
16x^2-9y^2
Answer is 16x^2-9y^2
[tex]\huge{\boxed{16x^2-9y^2}}[/tex]
Use the FOIL method.
First term in each binomial: [tex]4x*4x=16x^2[/tex]
Outside terms: [tex]4x*-3y=-12xy[/tex]
Inside terms: [tex]3y*4x=12xy[/tex]
Last term in each binomial: [tex]3y*-3y=-9y^2[/tex]
Add these all together. [tex]12xy-12xy+16x^2-9y^2=\boxed{16x^2-9y^2}[/tex]
a standard number cube is tossed. find p(3 or odd)
Answer:
0.5 or 1/2
Step-by-step explanation:
Let A be the event that the number cube is 3 or odd as 3 is also an odd number. So the event space will be:
{1,3,5}
The total number of outcomes are 6 as in:
{1,2,3,4,5,6}
So the probability of tossing 3 or odd number will be:
P(A) = n(A) / n(S)
= 3/6
=1/2
Hence the probability in fraction form is 1/2 and in decimal form is 0.5 ..
in The Given Parallelogram, Find the value of x and the measure of angle C.
Check the picture below.
bearing in mind that adjacent angles in a parallelogram are supplementary angles.
four thrids times the sum of a number 8 is 24. what is the numver
Answer:
The number is 10
Step-by-step explanation:
Let the number be x.
four thirds times = 4/3
According to the statement:
four thrids times the sum of a number and 8 is 24
4/3 *(x+8)= 24
Move 3 to the R.H.S and Multiply 4 with the parenthesis.
4x+32=24*3
4x+32=72
Move constant to the R.H.S
4x=72-32
4x=40
Divide both the terms by 4
4x/4=40/4
x=10
Therefore the number is 10....
Final answer:
To solve the equation, which is four thirds times the sum of a number and 8 equals 24, we isolate the variable by dividing by four thirds and subtracting 8 from both sides, resulting in the number being 10.
Explanation:
The student's question is asking to solve an algebraic equation. Specifically, the equation is: four thirds times the sum of a number and 8 equals 24. To find the number, represented by a variable, we'll denote it as x and translate the statement into the following equation: (4/3) × (x + 8) = 24.
First, we need to divide both sides of the equation by 4/3 to isolate the sum on one side:
(x + 8) = 24 × (3/4)
(x + 8) = 18
Now, subtract 8 from both sides to solve for x:
x = 18 - 8
x = 10
The final answer is that the number is 10. This is obtained through a step-by-step explanation solving the initial equation.
Where does f(x) = 3x2 – 11x - 4 intersect the x-axis?
Answer:
The x-intercepts are (4,0) and (-1/3,0).
Step-by-step explanation:
f or any relation/function will intersect the x-axis when y is 0.
Set that's what we will do is set y to 0 and solve for x.
0=3x^2-11x-4
I'm going to attempt to factor.
a=3
b=-11
c=-4
We need to find two numbers that multiply to be ac and add up to be b.
ac=-12=-12(1)
b=-11=-12+1
Let's factor 3x^2-11x-4 by grouping.
3x^2-11x-4
3x^2-12x+1x-4 ; I replaced -11x with -12x+1x
Group the first 2 pairs and group the last two pairs like so:
(3x^2-12x)+(1x-4)
Now factor what you can from each pair:
3x(x-4)+1(x-4)
Now you have two terms, both with the common factor (x-4) so factor it out:
(x-4)(3x+1)
Now let's go back to solving:
3x^2-11x-4=0
This is the same as solving:
(x-4)(3x+1)=0 (because this is just the factored form of the original equation.)
Now this means either x-4=0 or 3x+1=0.
We need to solve both.
x-4=0 can be solved by adding 4 on both sides resulting in x=4.
3x+1=0 requires two steps.
3x+1=0
Subtract 1 on both sides:
3x=-1
Divide both sides by 3:
x=-1/3
The x-intercepts are (4,0) and (-1/3,0).
Answer:
The negative x-intercept is at (-1/3 , 0).
The positive x-intercept is at (4 , 0).
Explanation:
Where does f(x) = 3x2 – 11x – 4 intersect the x-axis?
The negative x-intercept is at (-1/3 , 0).
The positive x-intercept is at (4 , 0).
Set f(x) equal to zero so
3x2 – 11x – 4 = 0
Plug in a. b, and c into the quadratic formula
and get 2 solutions:
1/3 and -4
take the opposite signs and put it in the x intercepts
D(-3,5)
What is the perimeter of square ABCD?
A(3,4)
+
37 units
cb
4/37 units
28 units
37 units
.
-54-3 -2 -
2
3
4
5
C(-4-1)
B(2,-2)
Answer:
[tex]4\sqrt{37} units[/tex] is the perimeter of square ABCD.
Step-by-step explanation:
Coordinates of square ABCD:
A = (3,4), B = (2,-2), C = (-4-1) , D = (-3,5)
Distance formula: [tex](x_1,y_1),(x_2,y_2)[/tex]
[tex]d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
Distance of AB: A = (3,4), B = (2,-2)
[tex]AB=\sqrt{(2-3)^2+(-2-4)^2}[/tex]
[tex]AB=\sqrt{(-1)^2+(-6)^2}=\sqrt{37} units[/tex]
Given that the ABCD is square, then:
AB = BC = CD = DA
Perimeter of the square ABC = AB +BC + CD + DA
[tex] AB+ AB+ AB+ AB= 4AB=4\sqrt{37} units[/tex]
[tex]4\sqrt{37} units[/tex] is the perimeter of square ABCD.
the postage required to mail a box depends on its weight
Jesse should use kilograms to weigh the package for postage.
Explanation:Jesse should use kilograms to weigh the package for postage. The books and documents in the box would likely weigh more than grams, so a larger unit of measurement is needed. Kilograms are a commonly used metric unit for measuring weight, and they are suitable for weighing the package accurately and determining the postage required.
87 is 15% of what number
Answer:
580
Step-by-step explanation:
Let's translate this word for word.
87 is 15% of what number
87 = 15% times x
87=.15 times x
[tex]87=.15 \cdot x[/tex]
Divide both sides by .15
[tex]\frac{87}{.15}=\frac{.15x}{.15}[/tex]
Cancel out the common factor of .15 on the right; that is .15/.15=1.
[tex]580=x[/tex]
580 is the number
Answer:
580
Step-by-step explanation:
Alright. Translate that into math, and you get:
87=15/100x
multiply both sides by x
8700/15=x
x=8700/15
x=580
Check:
580*15/100
58*15/10
870/10
87
BINGO!
v= -3i-4sqrt2, find a unit vector that points in the opposite direction as v
Answer:
The unit vector in the opposite direction of u is:
[tex]\vec{u} =-\frac{1}{\sqrt{23}}<-3i-4,\sqrt{2}>[/tex]
Step-by-step explanation:
To find the unit vector suppose u that points in the opposite direction as v
[tex]\vec{v}=<-3i,-4\sqrt{2}>[/tex]
we use the formula:
[tex]\vec{u} =-\frac{1}{||\vec{v}||}\vec{v}[/tex]
Finding [tex]||\vec{v}||[/tex]
[tex]||\vec{v}|| = \sqrt{x^2+y^2}\\||\vec{v}|| = \sqrt{(3i)^2+(4\sqrt{2}^2} \\||\vec{v}|| = \sqrt{9i^2+(16*2)}\\ i^2 = -1\\||\vec{v}|| = \sqrt{9(-1)+32}\\||\vec{v}|| = \sqrt{-9+32}\\||\vec{v}|| = \sqrt{23}[/tex]
[tex]\vec{u} =-\frac{1}{\sqrt{23}}<-3i,-4\sqrt{2}>[/tex]
The unit vector in the opposite direction of u is:
[tex]\vec{u} =-\frac{1}{\sqrt{23}}<-3i,-4\sqrt{2}>[/tex]
PLEASE HELP ASAP WILL MARK BRAINLIEST
Answer:
[tex]\sin \frac{3\pi}{2} = -1[/tex]
[tex]\cos\frac{3\pi}{2} =0[/tex]
Step-by-step explanation:
Please refer to the image attached.
Here we have a circle with unit radius. At some angle Ф the radius = 1 , and it is the hypotenuse (shown by green line in the image attached) of the ΔPQR thus formed. As our angle Ф increases, the hypotenuse gets closer to the positive y axis and at 90°, it overlap the y axis. Hypotenuse (H) and Opposite site (O) becomes same and Adjacent (A) becomes 0.
As our angle move further and reaches 180, the Hypotenuse and adjacent becomes same and overlap negative x axis. As we move further at 270 i.e [tex]\frac{3\pi}{2}[/tex] , the hypotenuse and opposite side overlap on y axis and Adjacent side become 0. However the opposite side becomes negative here .
Our sine ratio says
[tex]\sin \frac{3\pi}{2} =\frac{opposite}{Hypotenuse}[/tex]
[tex]\sin \frac{3\pi}{2} =\frac{-1}{1}[/tex]
[tex]\sin \frac{3\pi}{2} =-1[/tex]
Hence we have our [tex]\sin \frac{3\pi}{2} = -1[/tex]
Now
[tex]\cos\frac{3\pi}{2} =\frac{Adjacent}{Hypotenuse}[/tex]
Adjacent as we discussed is 0 at [tex]\frac{3\pi}{2}[/tex]
[tex]\cos\frac{3\pi}{2} =\frac{0}{1}[/tex]
[tex]\cos\frac{3\pi}{2} =0[/tex]
What is the 8th term of this geometric sequence? 6, 48, 384, 3072, . . .
Answer:
a(8)=12582912
Step-by-step explanation:
The 8th term can be determined by the formula:
an = a1 * r^(n-1)
where
n = the term to be found = 8
a1 = 1st number
r = common ratio
Common ratio can be found by dividing the second term by the first term
= 48/6 = 8
Substitute the values in the formula
a(8) = 6 * 8^(8-1)
a(8) = 6 * 8^7
a(8)= 6*8*8*8*8*8*8*8
a(8) = 6 * 2097152
a(8)=12582912 ....
Therefore the 8th term is 12582912 ....
Answer:
12582912
Step-by-step explanation:
You simply need to start by finding the pattern. Divide the second number by the first (the answer is 8), then divide the third number by the second, so on and so on. You will see the answer is always 8 which means each number is getting multiplied by eight to reach the next term. Finally, multiply the last number in the sequence by your answer (8) until you reach the 8th term.
evaluate -3ab when a= -2 and b= -5
Answer:
-30
Step-by-step explanation:
-3ab original equation
-3(-2)(-5) . plug in numerical values
6(-5) . -3 times -2 is 6
-30 . 6 times -5 is -30.
Answer:
-30
Step-by-step explanation:
Plug in -2 for a & -5 for b in the expression given:
-3ab = (-3)(-2)(-5)
Multiply across. Note that:
Negative number x negative number = positive number.
Positive number x negative number = negative number.
(-3)(-2)(-5) = (6)(-5) = -30
-30 is your answer.
~
If the sum of the zereos of the quadratic polynomial is 3x^2-(3k-2)x-(k-6) is equal to the product of the zereos, then find k?
Answer:
2
Step-by-step explanation:
So I'm going to use vieta's formula.
Let u and v the zeros of the given quadratic in ax^2+bx+c form.
By vieta's formula:
1) u+v=-b/a
2) uv=c/a
We are also given not by the formula but by this problem:
3) u+v=uv
If we plug 1) and 2) into 3) we get:
-b/a=c/a
Multiply both sides by a:
-b=c
Here we have:
a=3
b=-(3k-2)
c=-(k-6)
So we are solving
-b=c for k:
3k-2=-(k-6)
Distribute:
3k-2=-k+6
Add k on both sides:
4k-2=6
Add 2 on both side:
4k=8
Divide both sides by 4:
k=2
Let's check:
[tex]3x^2-(3k-2)x-(k-6) \text{ with }k=2[/tex]:
[tex]3x^2-(3\cdot 2-2)x-(2-6)[/tex]
[tex]3x^2-4x+4[/tex]
I'm going to solve [tex]3x^2-4x+4=0[/tex] for x using the quadratic formula:
[tex]\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
[tex]\frac{4\pm \sqrt{(-4)^2-4(3)(4)}}{2(3)}[/tex]
[tex]\frac{4\pm \sqrt{16-16(3)}}{6}[/tex]
[tex]\frac{4\pm \sqrt{16}\sqrt{1-(3)}}{6}[/tex]
[tex]\frac{4\pm 4\sqrt{-2}}{6}[/tex]
[tex]\frac{2\pm 2\sqrt{-2}}{3}[/tex]
[tex]\frac{2\pm 2i\sqrt{2}}{3}[/tex]
Let's see if uv=u+v holds.
[tex]uv=\frac{2+2i\sqrt{2}}{3} \cdot \frac{2-2i\sqrt{2}}{3}[/tex]
Keep in mind you are multiplying conjugates:
[tex]uv=\frac{1}{9}(4-4i^2(2))[/tex]
[tex]uv=\frac{1}{9}(4+4(2))[/tex]
[tex]uv=\frac{12}{9}=\frac{4}{3}[/tex]
Let's see what u+v is now:
[tex]u+v=\frac{2+2i\sqrt{2}}{3}+\frac{2-2i\sqrt{2}}{3}[/tex]
[tex]u+v=\frac{2}{3}+\frac{2}{3}=\frac{4}{3}[/tex]
We have confirmed uv=u+v for k=2.
the delivery ramp at the corner cafe id a right triangle. The hypotenuse is 4 meters long. One leg is 3 meters long. What is the length of the other leg
f. sqrt 7 meters
g. sqrt 12 meters
h. 3.5 meters
j. 5 meters
Answer:
f. sqrt 7 meters
Step-by-step explanation:
we use Pythagoras' theorem here,
let the unknown side be x,
therefore,
=> 3² + x² = 4²
=> x² = 16 - 9
=> x = √7 m
Answer:
f. sqrt 7 meters
Step-by-step explanation:
Since this is a right triangle, we can use the Pythagorean theorem to solve. We know the hypotenuse is 4 and one leg is 3. We want to solve for the other leg.
a^2 +b^2 = c^2 where a and b are the legs and c is the hypotenuse.
Substituting into the equation
3^2 + b^2 = 4^2
9+b^2 = 16
Subtracting 9 from each side
9-9+b^2 = 16-9
b^2 =7
Taking the square root of each side
sqrt(b^2) = sqrt(7)
b = sqrt(7) meters
Use the function y=0.0875x^2 - `10.5x + 436.25 calculate the number of accidents that occur at 60 km/h? Select the right answer.
Answer:
About 121.25
Step-by-step explanation:
Step 1: Interpret x and y
y is the number of accidents that occur = ?
x is the speed = 60 km/h
Step 2: Substitute value of x in the equation
y=0.0875x² - 10.5x + 436.25
y=0.0875(60)² - `10.5(60) + 436.25
Step 3: Find the value of y
y=0.0875(60)² - `10.5(60) + 436.25
y = 121.25
Therefore, the right answer is the last option which is 'about 121.25.'
!!
Which statement is true?
Answer:
Answer choice A.
Step-by-step explanation:
The y-intercept is the -8 for the g(x) equation. The chart shows that when x=0, y=-4. This is the y-intercept for f(x). -8 is less than -4.
Answer:
A. The y-intercept of g(x) is less than the y-intercept fo f(x).Step-by-step explanation:
[tex]\text{x-intercept is for y = 0}\to(x,\ 0)\\\\\text{y-intercept is for x = 0}\to(0,\ y)\\\\f(x):\\\\\text{From the table:}\\\\(0,\ -4)\to\text{y-intercept is -4}\\(16,\ 0)\to\text{x-intercept is 16}[/tex]
[tex]g(x)=4\sqrt{x}-8\to y=4\sqrt{x}-8\\\\\text{x-intercept:}\\\text{put y = 0 to the equation of the function}\\\\4\sqrt{x}-8=0\qquad\text{add 8 to both sides}\\4\sqrt{x}=8\qquad\text{divide both sides by 4}\\\sqrt{x}=2\to x=2^2\\x=4\leftarrow \text{x-intercept}\\\\\text{y-intercept:}\\\text{put x = 0 to the equation of the function}\\\\y=4\sqrt0-8\\y=0-8\\y=-8\leftarrow\text{y-intercept}[/tex]
(2,5) and (3/2 ,2) find the slope of the line passing through the points.
Answer:
6
Step-by-step explanation:
To find the slope 'm' we use 2 points from the line, those are given in the statement:
[tex]x_{1} =2\\y_{1} =5\\\\x_{2} =3/2\\y_{2} =2[/tex]
[tex]m=\frac{y_{2} -y_{1} }{x_{2}-x_{1}}[/tex]
[tex]m=\frac{2 -5 }{3/2-2}}[/tex]
Finally m=6
here are some ingredients for Bolognese sauce:
400g mince beef
800g chopped tomatoes
600ml stock
300ml red wine
kubby only has 300g minced beef
how much of all the other ingredients should she use???
Answer:
600g chopped tomatoes
450ml of stock
225ml of red wine
Step-by-step explanation:
Times them all by 0.75
If f(x)=5x , what is f-1 (x)?
Answer: The inverse is x/5
===============================================
How I got this answer:
The original function has 5x or 5*x, which reads out "five times x"
We have some unknown number x and we are multiplying it by 5. The inverse function undoes everything the original f(x) function does. Since the opposite of multiplicaiton is division, this means our answer involves dividing by 5.
--------
Here is a more algebraic explanation
f(x) = 5x
y = 5x .... replace f(x) with y
x = 5y
5y = x
y = x/5 .... divide both sides by 5 (to undo the multiplication)
g(x) = x/5 .... replace y with g(x)
here g(x) represents the inverse of f(x)
One useful property of inverses is that f( g(x) ) = g( f(x) ) = x
Alex originally paid $5200 for her car 1 year ago. The value of her car now is $4,420. What is
the percent of decrease in the value of her car?
Answer:
15%
Step-by-step explanation:
Which angle in
ABC has the largest measure?
Answer:
angle B
Step-by-step explanation:
how many dollars are in 100 grand?
Answer:
100,000 dollars.
Step-by-step explanation:
One grand = 1,000$
Multiply.
100 × 1,000
=100,000$
Do you prefer to express solutions to inequalities using interval notation or as an inequality ? Do you think it’s important to know both formats ? How could each be used ?
Answer:
I prefer to express solutions to inequalities using interval notation. Both formats are are important but I think interval notation is easier to understand and represents better the solutions.
For example, if you have the following inequation:
x-2> 1
x>3
Therefore, the solution could be written either x>3 OR (3, +inf). But what happens if the solution to the system of equation is x>3 or x<-3? The solution can be easily written as: (-inf, -3) U (3, inf) instead of 'x>3 or x<-3' which can be confusing.
A machine cuts a strip of carpet into two pieces. The length of the smaller piece is 5 meters greater than the length of the larger piece. If the length of the smaller piece is 12 meters, the length of the bigger piece is meters and the total length of the carpet is meters.
Answer:
Length of larger piece: 7 m
Total length of carpet is: 19 m
Step-by-step explanation:
Let the smaller piece have length x.
Let the larger piece have length y.
"The length of the smaller piece is 5 meters greater than the length of the larger piece."
x = y + 5
"If the length of the smaller piece is 12 meters"
x = 12
x = y + 5
12 = y + 5
7 = y
y = 7
The larger piece has length 7 meters.
The total length of the carpet is x + y = 12 m + 7 m = 19 m
To find the length of the larger piece of carpet, use the equation x + 5 = 12, and solve for x. Substitute the total length of the carpet for x in the formula to find the length of the larger piece.
Explanation:The problem involves finding the length of the larger piece of carpet when the length of the smaller piece and the total length of the carpet are known. Let's assume the length of the larger piece is x meters. According to the problem, the length of the smaller piece is 5 meters greater than the length of the larger piece, so the length of the smaller piece can be represented as x + 5 meters. The total length of the carpet is the sum of the lengths of the smaller and larger pieces, so we can create the equation: x + (x + 5) = total length. Given that the length of the smaller piece is 12 meters, we can substitute x + 5 with 12 in the equation and solve for x:
x + (x + 5) = total length
x + x + 5 = total length
2x + 5 = total length
2x = total length - 5
x = (total length - 5) / 2
Now we have the formula to calculate the length of the larger piece. Simply substitute the total length of the carpet into the formula to find the length of the larger piece.
Learn more about carpet length here:https://brainly.com/question/27911756
#SPJ12